The Rate of Interest Under Ideal Conditions - Samuelson, Paul A. (Quarterly Journal of Economics, 1939)
Implications of Ideal Conditions, 286. — Entrepreneurial behavior with a given rate of interest, 287. — Individual behavior with a given rate of interest, 290. — The identity between Saving and Investment, 292. — The determination of the rate of interest, 295. — Distinguishable components of the process of capital growth, 296. — The assumption of perfect certainty, 297.